Hydroxychloroquine attenuates cigarette smoke induced autophagic signaling in the mouse ovary - Furlong, H. C. (2016)
We previously demonstrated that Cigarette Smoke (CS) induces autophagy in the ovary. Therefore we aimed to determine if chloroquine (CQ) could inhibit CS-induced autophagy in the ovary. Eight week old mice were implanted with CQ pellets; 0, 25, and 50 mg CQ/kg. Half of the animals in each group were exposed to room air and the other half were exposed to CS twice daily for 8 weeks. Ovaries were harvested for electron microscopy, gene and protein expression analysis. There was a significant increase in the production of autophagosomes in granulosa cells of mice exposed to CS (p = 0.0297). However 25 and 50 mg/kg CQ treatment significantly decreased the CS-induced autophagosomes (p = 0.0505; p = 0.0065) and attenuated the effects of CS on LC3B and BECN1 expression. In summary, this suggests that CQ attenuates CS-induced autophagy in the ovary and that ovarian protection from toxic insult is potentially feasible.